IMPLEMENTASI METODE BERNYANYI DALAM PEMBELAJARAN BAHASA ARAB PADA ANAK USIA DINI DI TK AISYIYAH BUSTANUL ATHFAL IV PALU - Nursyam, Nursyam (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
This study aims to describe the implementation of learning the Arabic language with singing method. Problematic in teaching Arabic is to singing and to know the common efforts of teachers in overcoming these problems. This study is a qualitative field by taking TK Aisyiyah Bustanul Atfal background. The data collection is done by conducting observation, interviews and documentation. Analysis of the data used there by means of descriptive analysis using inductive method. The results showed; 1.pelaksanaan learning Arabic with singing method quite effective. As evidenced by the many students who love to sing in Arabic, began to recognize Arabic and memorize mufradat given by the teacher. Problematic in this case there are a few that the linguistic problem is the sound system and vocabulary for children at an early age is not fluent in the pronunciation of the letters and memorize easily forgotten if not repeated. While the non-linguistic problem is the lack of educational background of teachers in this school Arabic, Arabic language lessons mufradat only limited recognition alone. The efforts of teachers in addressing these problems with the singing seek specific guidance Arabic language teacher and student roles. Reproduce songs from the Arabic language and the words replaceable, repeating rote and received a teacher of the PBA.